2015
DOI: 10.1016/j.jtcvs.2015.08.105
|View full text |Cite
|
Sign up to set email alerts
|

The impact of 6 weeks of atrial fibrillation on left atrial and ventricular structure and function

Abstract: Objective The impact of prolonged episodes of atrial fibrillation on atrial and ventricular function has been incompletely characterized. The purpose of this study was to investigate the influence of atrial fibrillation on left atrial and ventricular function in a rapid paced porcine model of atrial fibrillation. Methods A control group of pigs (group 1, n = 8) underwent left atrial and left ventricular conductance catheter studies and fibrosis analysis. A second group (group 2, n = 8) received a baseline ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 13 publications
0
12
1
1
Order By: Relevance
“…25,26 Striving for sinus rhythm as soon as possible when new-onset POAF occurs also is supported by a recent study that demonstrated that in a porcine model the left atrium underwent significant structural remodeling and decreased contractility after 6 weeks of AF. 27 Limitations A limitation of the present study is that we, because of its retrospective design, did not study patients with different treatment strategies on new-onset POAF. Therefore, we do not know whether the findings of the present study would still be valid in the event that new-onset POAF was treated in another way than in the present study.…”
Section: Discussionmentioning
confidence: 96%
“…25,26 Striving for sinus rhythm as soon as possible when new-onset POAF occurs also is supported by a recent study that demonstrated that in a porcine model the left atrium underwent significant structural remodeling and decreased contractility after 6 weeks of AF. 27 Limitations A limitation of the present study is that we, because of its retrospective design, did not study patients with different treatment strategies on new-onset POAF. Therefore, we do not know whether the findings of the present study would still be valid in the event that new-onset POAF was treated in another way than in the present study.…”
Section: Discussionmentioning
confidence: 96%
“…As described previously [ 9 ], 76% had no symptomatic AF recurrences or AF episodes on 24-h Holter recordings at 12 months follow-up. The success rate is important since AF may cause significant structural remodeling and decreased contractility of the left atrium [ 22 ] promoting thromboembolism [ 23 ]. In our study, there were no thromboembolic events during 12 months follow-up except for in the one patient in whom an adequate anticoagulation medication had not been followed which emphasizes the importance of adequate anticoagulation throughout the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Результаты после операции «Лабиринт» характеризуются восста-новлением синусового ритма, физиологическим проведением импульса по предсердиям, нали-чием предсердного вклада и ремоделированием предсердий (рис. 3) [13,[25][26][27].…”
Section: Discussionunclassified